Institutional Proximity as Strategy: A Typology of Lithuanian and Polish Leftist Feminisms - Bielousova, Gražina (Sociologija. Mintis ir veiksmas, 2024)
This article examines the strategies and forms of action of leftist feminists in Lithuania and Poland by employing the concept of institutional proximity as an analytical tool. Based on ethnographic research conducted between 2022 and 2024, involving 20 activists, it proposes a tripartite typology that distinguishes the political, parapolitical, and transsocial realms of action. This typology enables analysis not only of political opportunity structures but also of the significance of strategic, ethical, and ideological decisions for the modalities of leftist feminism in the post-socialist context. The article treats leftist feminism as a decentralized social movement whose participants deliberately choose how far from institutional politics to position their actions in order to bring about the desired social change. The study reveals that women’s decisions to act in one realm or another are not static but dynamic, often shifting depending on the political climate, personal circumstances, and changes in power relations. This typology allows for an understanding of how the parapolitical level can become both a springboard into institutional politics and a space of withdrawal; how transsocial practices generate latent movement potential; and how institutional activity often entails compromises and internal conflict. The comparative analysis of Lithuania and Poland shows that, although Polish leftist feminists have a longer tradition of institutional political expression, they also face challenges characteristic of systemic sexism and the discrimination of women within political and social movements.
Keywords: leftist feminism; social movement typology; women’s social movements; feminism in Lithuania; feminism in Poland